ความสัมพันธ์ระหว่างแรงจูงใจในการเรียนรู้กับความผูกพันต่อองค์การโดยมีความปลอดภัยทางจิตใจเป็นตัวแปรกำกับ - วีระวัชร์ มงคลโชติ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This objective of this research is to study the relation between motivation to learn and organizational commitment as moderated by psychological safety. Participants were 176 Chulalongkorn University undergraduate students who participated in any extracurricular clubs or projects. The recruitment was done via Facebook and Line using convenience sampling and snowball sampling method. Data was collected via a 41-item online questionnaire measuring motivation to learn, psychological safety, and organizational commitment. The results showed that motivation to learn has a significantly positive direct effect on organizational commitment (β = .454, p < .001). The there is no moderation effect of psychological safety on the relation between motivation to learn and organizational commitment (β = -.085, p = .157). However, the results showed that psychological safety improves predictive ability on organizational commitment (β = .289, p < .001).